Bibliometric Analysis: Trends In Studies On Realistic Mathematics Education Learning to Enhance Mathematical Reasoning Abilities - Risantika Risantika; Effie Efrida Muchlis; Anny Sovia; Edi Susanto; Ringki Agustinsa (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematical reasoning is an important aspect of mathematics education that involves logical thinking, problem analysis, and drawing conclusions based on existing data. Realistic Mathematics Education (RME) connects mathematical concepts with real situations that train students' logical thinking so that reasoning skills tend to improve. Therefore, it is important to analyze the development of RME research on reasoning skills. This analysis presents a bibliometric analysis of the literature on RME-based learning to improve mathematical reasoning, using data from Google Scholar accessed through the Publish Or Perish software and analyzed with the help of VOSViewer software. Through keyword searches for "RME" and "Mathematical Reasoning", 167 relevant documents were analyzed based on performance analysis, citation metrics, co-words, and co- authorship networks. The analysis reveals that publications on RME-based learning to improve reasoning skills have increased recently, although from 2008 to 2016 it was less than 4 per year. Indonesia has made significant contributions to RME research, with many of its authors actively involved in this field. The analysis identifies recent trends in advancing reasoning skills, including exploring topics such as the use of technology, media integration, hybrid learning models, and various approaches in RME-based teaching. In addition, this analysis highlights the potential for further research on the use of student worksheets as a widely applied learning medium in RME-based education to improve mathematical reasoning.